Pengaruh Pelayanan Petugas Ruang Tunggu PT Angkasa Pura I Terhadap Kepuasan Pengguna Jasa di Bandar Udara Internasional Yogyakarta - Zakiah; Eny Sri Haryati (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2023)
Yogyakarta International Airport (YIA) is an international airport in the Special Region of Yogyakarta, Kulon Progo Regency in Kapanewon Temon. PT Angkasa Pura I must pay attention to services and facilities in the passenger departure waiting room because it is a service company. The purpose of this study is to determine the extent to which the services provided by PT Angkasa Pura I waiting room officers affect service user satisfaction at Yogyakarta International Airport and to find out how much influence the services of PT Angkasa Pura I waiting room officers on service user satisfaction at Yogyakarta International Airport. This study employs quantitative techniques. The information was gathered through conveying surveys to 100 respondents utilizing the lounge area of homegrown trips on November 1 to December 31, 2022. Information investigation was finished by utilizing straightforward direct relapse with the help of the lounge area staff as the autonomous variable and passanger fulfillment as the reliant variable. With a significance level of T = 16.293 > 1.661 and a 0.05 significance level, the findings demonstrate that passenger satisfaction is significantly influenced by the service provided by waiting room staff. The help of sitting area staff as the autonomous variable impacts traveler fulfillment by 73%. Meanwhile, variables outside of this study have an impact on the remaining 27%. The fact that Ha is accepted while Ho is rejected suggests that Yogyakarta International Airport's waiting room staff has a significant impact on passenger satisfaction.